Hubungan Pemahaman tentang Surat-Menyurat terhadap Kemampuan Menulis Surat Dinas Siswa Kelas VII SMP Negeri 9 Oku - Awalludin, Awalludin; Sanjaya, M. Rama; Bataria, Asmi (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
The ability to write student official letters is predicted to be influenced by an initial understanding of the material of the correspondence. For this reason, this study aims to: (1) find out the understanding of correspondence for Grade VII students of OKU 9 Public Middle School, (2) to determine the ability to write official letters for VII grade students of SMP Negeri 9 OKU, and (3) to find out the relationship between understanding of correspondence to the ability of Grade VII students of SMP Negeri 9 OKU to write official letters. The method used in this research is correlation method. The data collection technique used is a test. Data analysis technique used is descriptive statistical analysis techniques. Test results Based on the calculation of the correlation between the test data understanding correspondence with the ability to write official letter VII grade students of SMP Negeri 9 OKU obtained the value of r product moment at a significant level of 5% of 0.381 with rxy of 0.987. When compared to r arithmetic (rxy), then rxy is greater r product moment. That is, the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. Thus, it can be concluded that there is a significant relationship between the understanding of correspondence with the ability to write official letters for eighth grade students of SMP Negeri 9 OKU.